Environmental sustainability engagement practices among youths in Muallim District, Perak, Malaysia. Issue 1 (March 2021) - Mahat, H; Hashim, M; Saleh, Y; Nayan, N; Norkhaidi, S B; Mohamad, N F
Abstract: The study aimed to examine environmental sustainability practices among youths in Muallim District, Perak, Malaysia. This study applied a quantitative method comprising questionnaires with 400 youths aged 19 to 40. A simple random sampling method was used to divide the respondents into groups of two. Most variables (including knowledge, values and skills) were at high levels, but the environmental sustainability skills variable was only at a moderate level, with a mea score between 2.34 until 3.66. The findings also revealed a strong significant relationship between knowledge, values and environmental sustainability skills and environmental sustainability practices (p<0.05). The regression findings showed that environmental sustainability knowledge, environmental sustainability values and environmental sustainability skills contributed a total of 38.3 percent of variance change to environmental sustainability practices, with environmental sustainability knowledge being the greatest contributor at 31.5 percent, environmental sustainability at 5 percent and environmental sustainability skills at 1.8 percent (R2 =.383, F(1, 339)=81.846, p<.05). This indicates that overall environmental engagement practices were influenced by individual sustainability skills. In fact, environmental knowledge not create awareness among youths to apply practices that lead to environmental sustainability; rather, the skills possessed and acquired by youths can lead to their engagement in environmental sustainability practices.